Constraint-based verification. - Yuan, Jun, ....-; Aziz, Adnan, ....-; Pixley, Carl, ....- (New York : Springer, 2006)
Introduction.- Constrained Random Simulation.- High Level Verification Languages.- Assertion Languages and Constraints.- Preliminaries.- Constrained Vector Generation.- Constraint Simplification.- More Optimizations.- Constraint Synthesis.- Constraint Diagnosis.- Word-Level Constraint Solving.-